2020
DOI: 10.1002/lary.29254
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Feedback Control of Vocal Pitch in Spasmodic Dysphonia

Abstract: Objectives/Hypothesis Hearing plays an important role in the maintenance of vocal control in normal individuals. In patients with spasmodic dysphonia (SD), however, the ability to maintain sustained control of phonation is impaired. The origins of SD are unknown, and it is unclear whether auditory feedback‐dependent vocal control is compromised in these patients. Study Design Prospective case‐control study. Methods We tested 15 SD patients and 11 age‐matched controls. Voice recordings were performed while subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 43 publications
0
10
2
Order By: Relevance
“…Behaviourally, in the current study, patients and controls showed similar compensatory vocal responses, in spite of significant neural activation differences. In contrast to the current behavioural findings, a recent study found that patients with LD have a larger and earlier vocal pitch compensation response to pitch feedback perturbation 66 . However, there are a few notable differences in the stimuli between the two studies; the pitch shift in Thomas et al 66 was 200 cents (100 cents here) and lasted for 200ms (400ms here).…”
Section: Behavioural Responses To Pitch Feedback Perturbationscontrasting
confidence: 99%
See 4 more Smart Citations
“…Behaviourally, in the current study, patients and controls showed similar compensatory vocal responses, in spite of significant neural activation differences. In contrast to the current behavioural findings, a recent study found that patients with LD have a larger and earlier vocal pitch compensation response to pitch feedback perturbation 66 . However, there are a few notable differences in the stimuli between the two studies; the pitch shift in Thomas et al 66 was 200 cents (100 cents here) and lasted for 200ms (400ms here).…”
Section: Behavioural Responses To Pitch Feedback Perturbationscontrasting
confidence: 99%
“…In contrast to the current behavioural findings, a recent study found that patients with LD have a larger and earlier vocal pitch compensation response to pitch feedback perturbation 66 . However, there are a few notable differences in the stimuli between the two studies; the pitch shift in Thomas et al 66 was 200 cents (100 cents here) and lasted for 200ms (400ms here). The patients participating in our study were all pre-botox whereas Thomas et al 66 recruited patients before and after botox.…”
Section: Behavioural Responses To Pitch Feedback Perturbationscontrasting
confidence: 99%
See 3 more Smart Citations